(untitled) (Dhaka University Journal of Science, 2022)
The main objective of this research is to quantify evidence of the impact of green-space on fifteen health outcomes. Four databases- MEDLINE, EMBASE, AMED and CINAHL from January, 2000 to June, 2019 were searched. In this meta-analysis 63 observational studies were included for the investigation where 15 health outcomes (e.g., Type-2 Diabetes, Incidence of Hypertension, Incidence of Asthma, Stroke, Preterm Birth, Cardiovascular Mortality, All-cause Mortality, Salivary Cortisol and self-identified well-being etc) are considered. Our meta-analysis results revealed increased green-space exposure is associated with decreased heart rate (standardized mean difference (SMD)=−0.67), salivary cortisol (SMD = −0.31), along withreduced risk of preterm birth (OR = 0.87), type II diabetes (OR =0.76), hypertension (OR =0.77), coronary heart disease (OR = 0.85), all-cause mortality (OR = 0.69), cardiovascular mortality (OR =0.82), and an increased incidence of self-identified well-being (OR =1.15). Green-space exposure is found to be connected with the above mentioned health outcomes. Dhaka Univ. J. Sci. 69(3): 143-148, 2022 (June)